Spatial self–phase modulation patterns in graphene oxide and graphene oxide with silver and gold nanoparticles - Sadrolhosseini, Amir Reza; Suraya, Abdul Rashid; Shojanazeri, Hamid; Ahmad, Shukri Muhammad Noor; Nezakati, Hossein * (Springer, 2016)
The spatial self-phase modulation effect in graphene oxide with silver and gold nanoparticles were considered for demonstration of nonlinear properties of nanocomposites. Gold and silver nanoparticles were fabricated in graphene oxide using laser ablation at different times. The prepared samples were characterized using UV–Visible, transmission electron microscopy and X-ray diffraction spectroscopy. The absorption peaks in blue and green ranges were appeared related to silver and gold nanoparticles, and the nanoparticles were capped by graphene oxide in a spherical shape. The concentration of nanoparticles increased with an increased the ablation time. The nonlinear effect in graphene oxide and graphene oxide with gold and silver nanoparticles was then observed using the spatial self-phase modulation technique at 532 and 405 nm wavelength. Consequently, the self-defocusing effect was appeared in the mentioned medium, and the number of spatial self-phase modulation rings increased with an increased volume fraction of nanoparticles.